Predictive modelling and reliability analysis of aged, corroded pipelines - Ossai, Chinedu Ishiodu (Curtin University, 2016)
Pipeline corrosion is a major challenge facing many oil and gas industries today because of the enormous downtime associated with corrosion related failures. This research utilized field data for modelling the reliability of aged corroded pipelines via probabilistic-based modelling techniques that included Markov decision process. The models developed from this work have been used for estimating the remaining useful life of corroded pipelines and can potentially enhance the integrity of future operational pipelines.